Finite element analyses of corroded pipeline with single defect subjected to internal pressure and axial compressive stress. (July 2020) - Arumugam, Thibankumar; Karuppanan, Saravanan; Ovinis, Mark
Abstract: This paper describes the application of finite element method (FEM) and the development of equations to predict the failure pressure of single corrosion affected pipes subjected to internal pressure and axial compressive stress. The finite element analysis (FEA) results were verified against full-scale burst tests and theoretical calculations. Material non-linearity, which allow for large strains and displacements, were considered. In addition, true UTS instead of engineering UTS was used to determine the point of failure. The pipes used in the FEA was modelled based on API 5L X52 modified steel with a length of 2000 mm, a nominal outer diameter of 300 mm, and a nominal wall thickness of 10 mm. The results obtained from FEA were compared to that of existing comprehensive corrosion assessment method, known as DNV-RP-F101. Six equations, utilizing the Buckingham's π theorem and multivariate non-linear regression techniques, were developed for predicting the failure pressure of corroded pipeline with single defect subjected to both internal pressure and axial compressive stress. These equations provide improved failure pressure predictions with good margins of errors (less than 10%). Highlights: Axial compressive stress is detrimental to pipes with single corrosion defect. DNV is conservative with its failure pressure prediction. Finite element method provides better failure pressure predictions. Finite element analysis used to develop new failure pressure prediction equations.